“…He’s not beating me”—Socio-cultural construction of intimate partner violence and traditional birth attendants: implications for maternal & child health in rural communities in Hohoe, Ghana - Okoror, Titilayo A.; Nyamuame, Bless M.; Martin-Ikpe, Cordelia; Gilani, Yasmeen; Nyamuame, Samuel Elikem (Frontiers in Global Women's Health, 2024)
Most research on Intimate Partner Violence (IPV) focuses on the physical, sexual and psychological abuse, with less focus on the financial abuse. This study explores nursing mothers' experiences and perceptions of financial and material support from their significant others and traditional birth attendants' (TBA) observations of support to nursing mothers in their communities. Using purposive sampling, focus groups and interviews were conducted primarily in Ewe language among nursing mothers and TBAs in rural communities in Hohoe, Volta region, Ghana. All discussions were audiorecorded and transcribed for analysis. Thematic analysis guided by the social constructivist framework was used in data analysis. Twenty-seven women participated in the study, ranging in ages from 19 to 82 (20 nursing mothers; 7 TBAs). Most participants were married (19) and about 65% reported working outside the home (10 nursing mothers; 7 TBAs). Two themes emerged from the data analysis: Lack of support from partners for housekeeping chores and finances; and TBAs as mediators. Mothers who reported lack of financial support did not view lack of financial support as abuse, rather as hinderance to their efforts to care for their children. TBAs act as mediators interceding on behalf of mothers with their husbands and fathers of their children, while also seeking resources to support them. Understanding the perceptions and socio-cultural meanings women attached to IPV experience is essential for effective intervention to reduce IPV. In addition, TBAs can be a resource in intervening to alleviate IPV in their communities, thereby improving maternal and child health.